ВОСПРИЯТИЕ И ПРИНЯТИЕ ТЕХНОЛОГИЙ ИСКУССТВЕННОГО ИНТЕЛЛЕКТА ПРЕПОДАВАТЕЛЯМИ И КУРСАНТАМИ ВОЕННЫХ ОБРАЗОВАТЕЛЬНЫХ УЧРЕЖДЕНИЙ - Абдурахмонов Зафар Бaтирович (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This study examines the perception and acceptance of artificial intelligence (AI) technologies by faculty members and cadets in military higher education institutions. The aim is to evaluate their readiness for AI implementation, identify key barriers, risks, and motivating factors within the specific context of military education. The research employs analytical, structural-functional, and comparative methods, along with the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT). The findings reveal that cadets show significantly higher adaptability and positive attitudes toward AI compared to teachers, who maintain a more cautious, regulation-oriented stance emphasizing control, discipline, and information security. The study concludes that successful AI integration in military education requires a phased approach, robust normative regulation, and strict adherence to national security, ethical, and pedagogical standards.